2021
DOI: 10.1590/1806-9282.67.suppl1.20201063
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on the Cardiovascular System

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) induces coronavirus-19 disease , has affected many people in Brazil and worldwide. This disease predominantly affects the organs of the respiratory system, but it also damages the brain, liver, kidneys and especially the heart. In the heart, scientific evidence shows that this virus can damage the coronary arteries, generating microvascular dysfunction, favoring acute myocardial infarction. Furthermore, with the increased expression of pro-inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…COVID-19 is a disease that triggers a cytokine storm, leading to inflammation, fibrosis, and cell death [13,14]. These factors directly affect the morphology and functionality of various organs in the human body, including the brain, heart, and others [15][16][17][18]. In this context, ICU workers live in constant fear and insecurity, resulting in elevated levels of emotional stress, anxiety, and depression [19].…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 is a disease that triggers a cytokine storm, leading to inflammation, fibrosis, and cell death [13,14]. These factors directly affect the morphology and functionality of various organs in the human body, including the brain, heart, and others [15][16][17][18]. In this context, ICU workers live in constant fear and insecurity, resulting in elevated levels of emotional stress, anxiety, and depression [19].…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study by Wang et al analyzed 6,245,282 older adults (over 65 years old), and the authors showed that older people infected by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) were at significantly higher risk for a new diagnosis of Alzheimer's disease . Post-COVID neurological consequences are tightly linked to other systems, including changes in the cardiovascular and immune systems, as well as higher levels of stress, anxiety, and depression (Campos et al, 2019;Salari et al, 2020;Zubair et al, 2020;Improta-Caria et al, 2021;Júnior et al, 2021;Sousa et al, 2021). The enigmatic nature of the post-COVID syndrome's underlying mechanism necessitates intense investigation in order to achieve effective management strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Another recent study by Wang et al analyzed 6,245,282 older adults (over 65 years old), and the authors showed that older people infected by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) were at significantly higher risk for a new diagnosis of Alzheimer’s disease ( Wang et al, 2022 ). Post-COVID neurological consequences are tightly linked to other systems, including changes in the cardiovascular and immune systems, as well as higher levels of stress, anxiety, and depression ( Campos et al, 2019 ; Salari et al, 2020 ; Zubair et al, 2020 ; Improta-Caria et al, 2021 ; Júnior et al, 2021 ; Sousa et al, 2021 ). The enigmatic nature of the post-COVID syndrome’s underlying mechanism necessitates intense investigation in order to achieve effective management strategy.…”
Section: Introductionmentioning
confidence: 99%